Zirconia ceramics processing by intense electron and ion beams; Nuclear Instruments and Methods in Physics Research Section B: Beam Interactions with Materials and Atoms; Vol. 435, 15 November 2018 : International Conference on Radiation Effects in Insulators, July 2-7, 2017 in Versailles, France - Gyngazov (Ghyngazov) S. A. Sergey Anatolievich (2018, 2018)
Title screen